Tinjauan Fatwa DSN Terhadap Produk Pembiayaan Pada Pegadaian Syariah Cipto Cirebon - Kharisma Aurora; Alvien Septian Haerisma; Amir Amir (CIEBER: Contemporary Islamic Economic and Business Review, 2025)
This study examines the application of sharia principles in gold pawn products at Pegadaian Syariah Cipto Cirebon. The main issues identified are employees’ limited understanding of DSN-MUI fatwas, discrepancies between fatwa provisions and institutional regulations, and debates over the application of mu’nah (maintenance) fees. Using a qualitative descriptive method with field research through interviews, observations, and document analysis, the study assesses compliance with DSN-MUI Fatwas No. 25, 26, and 92. The findings show that the gold pawn financing mechanism generally complies with sharia principles through the use of hybrid contracts (rahn, qardh, and ijarah) and fair mu’nah fees that avoid riba, gharar, and maysir. However, DPS supervision remains suboptimal due to limited resources and weak coordination. The study recommends strengthening sharia supervision by enhancing DPS competence, aligning SOPs with DSN fatwas, and implementing regular sharia audits to ensure compliance and transparency.